“Carry each other’s burdens” Children’s aid missions in the Netherlands - Horváth, Erzsébet (Acta Neerlandica, 2015)
In the 20th century the Dutch government and the Dutch people undertook the mission of helping socially deprived children on several occassions. The Hungarian and the Dutch Reformed churches have been tied by a close, brotherly bond for several centuries. The major organizer of the children’s holiday scheme was László Pap, Reformed minister, professor of theology in Budapest. 500 children on board of the first train traveled to the Netherlands on July 12th, 1948 and on January 19th, 1949 they arrived home. All the children are perfectly happy in their host families. The children are more than satisfied with their host families and vice versa. They had also found many friends, brothers and sisters, and had become family members.